Association of infantile bruxism and the terminal relationships of the primary second molars - Tatiana Helena Junqueira; Ana Carla Raphaelli Nahás-Scocate; Karyna Martins do Valle-Corotti; Ana Claudia de Castro Ferreira Conti; Shirley Trevisan (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to analyze the association between infantile bruxism and the terminal relationships of the primary second molars. A total of 937 pre-school children (both genders), aged from 2 to 6 years, from municipal schools in São Paulo were evaluated. In this study, a questionnaire considering the bruxism habit and the presence of headaches and/or restless sleep was answered by the parents/guardians. A clinical exam of occlusion in the anteroposterior direction (vertical plane - VP, mesial step - MS and distal step - DS) was performed by the examiners in the school environment. Student's t test, Fisher's test and a logistic regression test were applied for the statistical analysis at a significance level of 5%. The prevalence of the bruxism habit was 29.3% among the total sample. Because there was no significant difference between the sides evaluated, the left side was taken as the standard. Among those children with bruxism, 25.7% presented a mesial step terminal relationship at the primary second molars, 29.1% had DS, and 30.2% had VP. Regarding the association of the parafunctional habit with the type of terminal relationship, no significant results were found. Children who slept restlessly or suffered from headaches were verified to show a higher chance of expressing the habit (OR = 2.4 and 1.6, respectively). The prevalence of bruxism in the studied sample was 29.3%, and its association with the primary second molars' terminal relationship was not statistically significant.